Session Topic: Monetary Policy and the Exchange Rate: Discussion - Cornell, W. Bradford; Ripley, Duncan M.; Protopapadakis, Aris (Journal of Finance, 1977)
W. Bradford Cornell, Duncan M. Ripley, Aris Protopapadakis, Session Topic: Monetary Policy and the Exchange Rate: Discussion, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 545-551